ANALISIS IMPLEMENTASI PENGEMBANGAN SUMBER DAYA MANUSIA (Studi pada Departemen Human Capital PT Surya Artha Nusantara Finance) - Diva Terry Anona; Arik Prasetya (Fakultas Ilmu Administrasi Universitas Brawijaya, 2016)
The objectives of this research are to identify and explain the implementation of people development management in PT. Surya Artha Nusantara Finance along with the performance of people development management of PT Surya Artha Nusantara Finance today. The type of research that is used in this research is descriptive research with a qualitative approach. The focus of research is divided into two parts, the first focus is about the implementation of people development in PT Surya Artha Nusantara Finance (SANF). The second focus is to know the performance of people development in PT Surya Artha Nusantara Finance today. The collection of data by the researcher is based on primary and secondary data. The results and issues evaluation which is undertaken from this research shows the implementation of people development SANF is in conformity with the Astra Human Capital Management (AHCM) consisting of Assessing Training Needs, Designing Training Program, Delivery Training, and Training Evaluation. The current performance of people development SANF is going through the stages of systematic and policies applied in the process of people development based on the company's needs for labor in the activities undertaken. Obstacles that occur during the people development a rise more dominant from the internal. Keywords: Human Resources, People Development, Human Capital Management ABSTRAK Tujuan penelitian adalah untuk mengetahui dan menjelaskan penerapan manajemen pengembangan SDM di PT. Surya Artha Nusantara Finance dan untuk mengetahui dan menjelaskan kinerja manajemen pengembangan SDM PT Surya Artha Nusantara Finance saat ini. Jenis penelitian yang digunakan adalah penelitian deskriptif dengan pendekatan kualitatif. Fokus penelitian dibagi menjadi dua bagian, yaitu fokus pertama adalah tentang penerapan pengembangan SDM PT Surya Artha Nusantara Finance. Fokus kedua yaitu mengetahui kinerja pengembangan SDM PT Surya Artha Nusantara Finance saat ini. Pengumpulan data yang dilakukan peneliti, berasal dari data primer dan data sekunder. Dari hasil penelitian dan evaluasi masalah yang dilakukan,implementasi Pengembangan SDM SANF sudah sesuai dengan Astra Human Capital Management (AHCM) yang terdiri dari Assessing Training Needs, Designing Training Program, Delivery Training, dan Training Evaluation. Kinerja pengembangan SDM SANF saat ini sudah melalui tahapan yang sistematis dan kebijakan yang diterapkan dalam proses pengembangan SDM didasarkan atas kebutuhan perusahaan akan tenaga kerja dalam aktivitas yang dilakukan. Hambatan-hambatan yang terjadi selama pengembangan SDM lebih dominan muncul dari internal perusahaan. Kata kunci: Manajemen Sumber Daya Manusia, Pengembangan SDM, Manajemen Human Capital.